2008
DOI: 10.1038/clpt.2008.57
|View full text |Cite
|
Sign up to set email alerts
|

Toward Personalized Therapy for Smoking Cessation: A Randomized Placebo-controlled Trial of Bupropion

Abstract: We examined whether a pretreatment phenotypic marker of nicotine metabolism rate (NMR) predicts successful smoking cessation with bupropion. Smokers (N = 414) were tested for pretreatment NMR, based on the ratio of 3′-hydroxycotinine/ cotinine derived during smoking, before entering a placebocontrolled randomized trial of bupropion plus counseling. At the end of the 10-week treatment phase, slow metabolizers (1st NMR quartile) had equivalent quit rates with placebo or bupropion (32%). Fast metabolizers (4th NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
195
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(204 citation statements)
references
References 30 publications
4
195
4
1
Order By: Relevance
“…In another clinical trial that tested the efficacy of bupropion for smoking cessation, smokers in the fourth NMR quartile (faster metabolizers) had poor smoking cessation rates if they were assigned the placebo treatment. However, bupropion offset the relapse liability among high NMR smokers (Patterson et al, 2008). Overall, these findings are consistent with the idea that smokers who rapidly metabolize nicotine might be more dependent and have greater difficulty with smoking cessation.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…In another clinical trial that tested the efficacy of bupropion for smoking cessation, smokers in the fourth NMR quartile (faster metabolizers) had poor smoking cessation rates if they were assigned the placebo treatment. However, bupropion offset the relapse liability among high NMR smokers (Patterson et al, 2008). Overall, these findings are consistent with the idea that smokers who rapidly metabolize nicotine might be more dependent and have greater difficulty with smoking cessation.…”
Section: Introductionsupporting
confidence: 82%
“…However, the groups did not differ with respect to overall nicotine withdrawal severity as assessed by the MNWS. As mentioned above, previous studies have found that smokers with high NMR had greater nicotine withdrawal severity and craving for cigarettes Rubinstein et al, 2008), although others did not find an association between NMR and craving or withdrawal (Patterson et al, 2008;Schnoll et al, 2009). The reasons for these conflicting findings remain to be determined.…”
Section: Discussionmentioning
confidence: 90%
“…However most people in these ethnic groups are not full poor metabolizers, with both alleles being fully null, rather they range from slow to intermediate, to normal, to fast nicotine metabolizers (Ho et al, 2009;Malaiyandi et al, 2005;). Thus, as people with the slowest rates of nicotine metabolism have the best quit rates in both placebo and nicotine replacement therapies (Ho et al, 2009;Lerman et al, 2006Lerman et al, , 2010Patterson et al, 2008;Ray et al, 2009), it is possible that slowing nicotine metabolism using inhibitors, along with nicotine, will combine the two effects observed in placebo and NRT treatment arms to increase the smoking cessation rates (Sellers et al, 2000;Tyndale et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…When smokers were categorized as normal or slow metabolizers on the basis of an NMR criterion, normal metabolizers (⩾0.35) smoked more cigarettes/day (Chenoweth et al, 2014), but slow metabolizers (o0.31) had a greater likelihood of 1-week abstinence from smoking (Chenoweth et al, 2014). When smokers were divided into quartiles based on NMR, the fastest metabolizers had a greater likelihood of abstinence from smoking with bupropion treatment than the slowest metabolizers (Patterson et al, 2008). According to the same quartile system, the slowest metabolizers had lower nicotine dependence, reported less cigarette craving following overnight abstinence, and less drug liking after intravenous nicotine compared to the fastest metabolizers (Sofuoglu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%